The Impact of Exchange Rate volatility on Banking Performance (case of Iran) - Nafiseh Keshtgar; Mosayeb Pahlavani; Seyed Hossein Mirjalili (International Journal of Business and Development Studies, 2020)
Banks play an important role in the Iranian economy which has a bank-based financial system. We examined the impact of exchange rate volatility as a determinant of banks' performance. In recent years, the exchange rate has been volatile in the Iranian economy and have an adverse effect on banks' performance. This study, investigate the issue for the period 2007-2017 for 14 Iranian banks. Exchange rate fluctuations are derived by GARCH method and the effect of its fluctuations on bank performance examined using panel data method. In order to evaluate banks' performance, we used two criteria, namely liquidity and profitability. Estimation of econometric model using panel data by random effects indicated that exchange rate volatility has a negative and statistically significant effect on banks' capital return ratio. Exchange rate volatility is also a determinant in increasing the ratio of lending to total bank deposits, as it increases the financial gap and creates the credit risk that the gap entails.
Keywords: N10; G01; E44; C22; 330; Volatility; Exchange Rate; Banks' Performance; Panel Data; Iranian Economy